Cervical necrotising fasciitis: a rare complication of infectious mononucleosis. Issue 3 (1st March 2019) - Din-Lovinescu, Corina; Berg, Howard
Abstract : Cervical necrotising fasciitis (NF) is an aggressive polymicrobial infection of the subcutaneous tissues in the head and neck. We present a case of a healthy 19-year-old man who developed cervical and upper mediastinal NF after an initial presentation of infectious mononucleosis (IM). He was treated with broad-spectrum antibiotics in addition to incision and drainage of an anterior neck and upper mediastinal abscess. He progressed favourably after ten days of hospitalisation and was discharged home on intravenous antibiotics. This is a unique case of cervical NF as a sequelae of IM in a previously healthy paediatric patient.